O możliwości technicznego uwarunkowania oboczności albo // abo w drukach polskich z XVI wieku - Osiewicz, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The article presents evidence of the use of variant forms albo // abo for typesetting purposes. To demonstrate this, the illustration material was used originating from five 16th-century prints in verse in which the form abo or albo appears only in long verses, brought to the right margin – which proves that the form was utilized because of its graphical and not linguistic features.